1979
DOI: 10.1037/0021-9010.64.5.483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recruiter authoritarianism and applicant sex on evaluation and selection decisions in a recruitment interview analogue study.

Abstract: The purpose of this study was to investigate the role of authoritarianism in subjects' judgments of male and female candidates in a job selection interview. Male and female personnel officers were randomly selected from a pool of 144 volunteers and were assigned on the basis of Revised California F Scale scores to high, moderate, and low authoritarian groups, until 14 males and 14 females comprised each treatment. It was hypothesized that high authoritarian personnel officers of both sexes (a) would rate male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Dichotomous sex-role conceptions within the authoritarian family emphasize exaggerated masculine and feminine characteristics[e.g. [71][72][73]. Johnson et al [74] found that authoritarian subjects from entrepreneurial backgrounds were more restrictive than nonauthoritarians in the number of behaviours they considered appropriate for children of both sexes.…”
Section: Religiosity and Decision Behaviour Patternsmentioning
confidence: 99%
“…Dichotomous sex-role conceptions within the authoritarian family emphasize exaggerated masculine and feminine characteristics[e.g. [71][72][73]. Johnson et al [74] found that authoritarian subjects from entrepreneurial backgrounds were more restrictive than nonauthoritarians in the number of behaviours they considered appropriate for children of both sexes.…”
Section: Religiosity and Decision Behaviour Patternsmentioning
confidence: 99%
“…Simas and McCarrey (1979) found that persons high in authoritarianism tended to evaluate males more favorably than persons lower on authoritarianism, but did not evaluate females less favorably.…”
Section: Age and Race Of The Intervieweementioning
confidence: 93%
“…Cotter et al (1982) found similar results with telephone interviews. Simas and McCarrey (1979) found that personnel officers high in authoritarianism (both male and female) tend to give male job applicants higher ratings than female applicants, after viewing videotaped simulated interviews.…”
Section: Age and Race Of The Intervieweementioning
confidence: 99%
“…Interviewer characteristics: Bernstein, Hakel, and Harlan (1975) found no important differences in ratings made by students and those made by interviewers other than students are more lenient in their ratings. Dipboye, Arvey, and Terpestra (1977) found males and females equally biased, while Simas and McCarrey (1979) found that highly authoritarian subjects rated male applicants more favorably than female applicants.…”
Section: B Interviewer Judgmentmentioning
confidence: 96%